The Implementation of Cloud Accounting in Indonesia: A Bibliometric Analysis - Molina; Dhieka Avrilia Lantana; Erwin Indriyanto; Kumba Digdowiseiso; Zalailah Salleh (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research adopts a bibliometric analysis approach to investigate the development of Cloud Accounting implementation in Indonesia in the 2018-2023 time period. Data was obtained via Google Scholar using keywords related to "Cloud Accounting in Indonesia". Search results were exported and analyzed using VOSViewer software to identify patterns, trends, and contributions of related researchers, journals, and conferences. The analysis involves mapping the distribution of keywords, researcher collaboration, annual publication evaluation, and article citation mapping. The research results show an exponential growth in researchers' interest in implementing Cloud Accounting in Indonesia. The increasing number of publications, peaking in 2023 with 147 publications, reflects the relevance of this topic in academic literature. Keyword analysis illustrates the shift in research focus from traditional aspects to “Cloud Accounting Adoption” and “SMES”. Research collaborations indicate active research groups, while journal analysis identifies influential academic platforms. Research themes that have not been widely explored, such as "Cloud Computing" and "Cloud Accounting Systems", represent future research opportunities. These findings provide in-depth insight into the implementation of Cloud Accounting in Indonesia, supporting academic and practical understanding in the context of the adoption of this technology.